Re-description of type material of Xenia Lamarck, 1816 (Octocorallia: Xeniidae) - Halász, Anna; Mcfadden, Catherine S.; Toonen, Robert; Benayahu, Yehuda (Zootaxa, 2019)
In this study we examined the original types of 21 of the 56 morphospecies of Xenia currently listed in WoRMS. Unfortunately, our attempts to locate additional type material failed, and we conclude that they have been lost. The type localities of the material examined include the Red Sea, West and Central Indian Ocean, the South Pacific, Indonesia, The Philippines, and the Bismarck Sea, reflecting the extensive biogeographical distribution of this genus throughout the Indo-Pacific Ocean. A neotype was designated from the northern Red Sea for X. umbellata, and sequencing established its position in the phylogenetic tree in relation to other genera of the family Xeniidae. In addition, X. flexibilis n. sp. was described from The Philippines. The findings from the current study led to the synonymizing of X. actuosa with X. sansibariana and of X. plicata with X. blumi. Overall, the study has re-described the types of 17 species considered to be valid based on morphological characters. Validation of the morphological features of original type material along with species-diagnostic genetic characters are required in order to facilitate our ability to correctly employ Latin binomials, both in phylogenetic studies and in any other biological surveys.